Molecular docking of 5-phenyl-5,6-dihydrotetrazolo- [1,5-c]quinazolines to penicillin-binding protein 2x (pbp 2x) and preliminary results of antifungal activity - Antypenko, O. M.; Antypenko, L.; Rebets, O.; Kovalenko, S. I.; Антипенко, Олексій Миколайович; Коваленко, Сергій Іванович (My University, 2022)
Affinity of thirteen 5-phenyl-5,6-dihydrotetrazolo[1,5-c]quinazolines and reference Tedizolid is calculated to penicillin-binding protein 2X (PBP 2X) (PDB ID: 2ZC4). The lead-compounds are proposed based on presented results, previous affinity towards ribosomal 50S protein L2P (2QEX), and their ADME profile. Besides, substance 12 has already shown good preliminary antifungal results towards C. albicans.
Antypenko O. M. - https://orcid.org/0000-0002-8048-445X; Kovalenko S. I. - https://orcid.org/0000-0001-8017-9108.
Keywords: 5-phenyl-5,6-dihydrotetrazolo[1,5-c]quinazolines; molecular docking; penicillin-binding protein 2X (PBP 2X); antifungal activity; C. Albicans